Cytological Spectrum of Pulmonary Histoplasmosis Diagnosed by Bronchoalveolar Lavage: 12 Years of Experience in French Guiana - Drak Alsibai, Kinan (J Fungi (Basel), 2021)
Disseminated histoplasmosis is a major cause of mortality in HIV-infected patients. Rapid and efficient diagnosis of Histoplasma capsulatum is crucial. Cytopathology is available in most hospitals and represents a rapid diagnostic alternative. In this study, we reviewed 12 years of experience to describe the cytology of histoplasmosis diagnosed by bronchoalveolar lavage (BAL) in relation to patient characteristics. BAL-diagnosed pulmonary histoplasmosis concerned 17 patients (14 HIV+). BAL cellularity ranged from 76,000 to 125,000 cells/mL in HIV patients, and 117,000 to 160,000 cells/mL in non-HIV patients. Macrophages predominated in all HIV patients (from 60% to 88%), lymphocytic infiltrates ranged from 5% to 15%, and neutrophils were very heterogeneous (from 2% to 32%). The number of H. capsulatum at hot spots seemed greater in HIV-infected than in immunocompetent patients (9 to 375 vs. 4 to 10) and were inversely proportional to the CD4 counts. Yeasts were both intracellular and extracellular in 85.7% of the HIV patients. This is the most comprehensive series detailing the cytological aspects of BAL in the diagnosis of H. capsulatum, focusing on the number of yeasts and their clustering pattern. The cytological examination of the Gomori-Grocott-stained BAL allows a reliable diagnosis of histoplasmosis.